Central neurogenic hyperventilation related to post-hypoxic thalamic lesion in a child - Pinar Gençpinar; Kamil Karaali; Şenay Haspolat; Oğuz Dursun (Neurology International, 2016)
Central neurogenic hyperventilation (CNH) is a rare clinical condition, whose mechanism is still unclear. Here, we report a 3-year-old male patient, who had bilateral thalamic, putaminal and globus pallideal infarction resulted in CNH without brainstem involvement. This case may illustrate a possible role for the thalamus in regulating ventilation.